Islam and Science Relation: A Critical Analysis of Contemporary Scientific Atheism of Richard Dawkins - Fasya Tharra Annada; Muhammad Faqih Nidzom (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2025)
Richard Dawkins, the most prominent figure of New Atheism, maintains that God and religion can be examined scientifically, positioning the theory of evolution as the central foundation of his argument. For Dawkins, evolutionary theory provides the best explanation for the origin of the universe's complexity, thereby rendering the existence of God unnecessary and setting science in direct opposition to religion. This study critically analyzes Richard Dawkins' scientific atheism from the perspective of the Islamic worldview using a qualitative approach through content analysis of Dawkins' primary works and relevant secondary literature. The findings reveal that Dawkins' rejection of the supernatural and his claim that science is the sole path to truth are rooted in the worldview of scientific naturalism, which reduces reality to its material dimensions while denying any non-empirical aspects of existence. This stands in sharp contrast to the Islamic worldview, which affirms from the outset that the universe is God's creation and that science serves as a means to understand and study nature to strengthen faith in Him. Unlike scientific naturalism, which positions science and religion as mutually contradictory, Islam presents an integrated vision where scientific inquiry and religious faith are complementary rather than oppositional. Consequently, contemporary Muslim scholars have promoted the Islamization of science to protect the Muslim community from the philosophical implications of modern science that marginalize God and religion.